Individual Learning Gains and Practical Effect of Cooking Class-Based Learning on Fine Motor Development in Early Childhood - Nur Indah Sari; Rahmawati Jamil Hasibuan (International Journal of Science and Society (IJSS), 2026)
Fine motor development in early childhood requires meaningful, hands-on, and developmentally appropriate learning experiences. Cooking activities provide children with opportunities to perform coordinated hand and finger movements while engaging in contextual learning. However, group average scores alone may not fully describe how individual children respond to a learning intervention. This study aimed to analyze individual learning gains and the practical effect of cooking class-based learning on fine motor development among children aged 5–6 years. A quantitative quasi-experimental approach with a pretest-posttest control group was employed involving 40 children at RA Baitul Ibadah, Binjai Barat, consisting of 20 children in an experimental group and 20 children in a control group. Data were collected using an observation instrument assessing children's fine motor performance and analyzed using absolute learning gain, normalized gain, standardized effect size, and probability of superiority. The experimental group increased from a mean pretest score of 23.80 to a posttest score of 37.55, producing a mean gain of 13.75 points. The control group increased from 19.30 to 26.75, producing a mean gain of 7.45 points. The difference in mean gain between groups was 6.30 points. The standardized effect size was approximately 1.68 based on Hedges' g, indicating a large practical effect. Furthermore, 90% of children in the experimental group achieved at least a moderate normalized gain, compared with 45% in the control group. These findings indicate that structured cooking class activities provide a substantial practical advantage for fine motor development. Cooking activities can therefore be integrated into early childhood learning as an experiential strategy for stimulating children's fine motor abilities while maintaining appropriate safety supervision.